2020
DOI: 10.1101/2020.01.07.894535
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TCF-1 regulates the stem-like memory potential of HIV-specific CD8+ T cells in elite controllers

Abstract: Although many HIV cure strategies seek to expand HIV-specific CD8+ T cells to control the virus, all are likely to fail if cellular exhaustion is not prevented. A loss in stem-like memory properties (i.e., the ability to proliferate and generate secondary effector cells) is a key feature of exhaustion; little is known, however, about how these properties are regulated in human virus-specific CD8+ T cells. We found that virus-specific CD8+ T cells from humans and non-human primates naturally controlling HIV/SIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…We found that SIV-specific CD8 + T cells from SICs expressed higher levels of TCF-1 than cells from VIRs, and these differences were more visible among less differentiated subsets and coupled with an enhanced expression of CXCR5, which may reflect the potential of these cells to migrate to germinal centers. During the revision of this manuscript, a preprint became available describing similar findings in cells from both HICs and SICs in an independent study (Rutishauser et al, 2020). In that study, the authors linked the expression of TCF-1 with the capacity of HIV-specific CD8 + T cells to expand.…”
Section: Discussionmentioning
confidence: 93%
“…We found that SIV-specific CD8 + T cells from SICs expressed higher levels of TCF-1 than cells from VIRs, and these differences were more visible among less differentiated subsets and coupled with an enhanced expression of CXCR5, which may reflect the potential of these cells to migrate to germinal centers. During the revision of this manuscript, a preprint became available describing similar findings in cells from both HICs and SICs in an independent study (Rutishauser et al, 2020). In that study, the authors linked the expression of TCF-1 with the capacity of HIV-specific CD8 + T cells to expand.…”
Section: Discussionmentioning
confidence: 93%
“…Finally, one of our most intriguing results was the profound downregulation of TCF1 in CD4 + T cells at both the transcriptional and protein levels. Although TCF1 is conventionally viewed as an effector of the canonical Wnt pathway (68) and recently reached notoriety for its role in maintaining stemness of antigen-specific memory CD8 + T cells (26,69), TCF1 has a plethora of functions in T cell development and differentiation largely independent of Wnt signaling (22). In CD4 + T cells, TCF1 has been implicated in orchestrating all the major Th subsets, including Th1, Th2, Th17 and Tfh (70).…”
Section: Discussionmentioning
confidence: 99%
“…TCF-1 is a major T cell transcription factor which controls T cell development and lineage, and also has an important role in T cell responses to infection 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 40 . However, the role of TCF-1 in controlling mature T cells following normal development has not been well studied.…”
Section: Discussionmentioning
confidence: 99%
“…However, TCF-1 is a critical T cell transcription factor for T cell development, CD4/CD8 lineage maintenance, and responses to infection 25, 26, 27, 28, 29, 30, 31, 32 , so global deficiency of this factor drastically influences T cell development and function 33 . It is unknown whether TCF-1 deficiency in mature T cells has a similar effect on FOXP3.…”
Section: Introductionmentioning
confidence: 99%